Comparative study between homeopathy and nimesulide on the prevention of bone resorption in experimental periodontitis in rats - Oliveira, Thais Marchini; Centurion, Bruna; Gigliotti, Mariana; Mergulhão, Tiago; Sakai, Vivien; Dionísio, Thiago; Faria, Flávio; Garlet, Gustavo Pompermaier; dos Santos, Carlos Ferreira (Revista da Faculdade de Odontologia de Porto Alegre, 2010)
Periodontitis is a chronic disease characterized by bone loss and inflammatory changes. We studied the effect of a homeopathic agent (Mercúrios Corrosivos 6 CH) and a non-steroidal anti-inflammatory drug (nimesulide) on the alveolar bone loss progression in experimentally induced periodontitis in rats. Sixty (60) Wistar rats were separated into group 1 (homeopathy), group 2 (nimesulide) and group 3 (saline solution). Silk ligatures were placed at the gingival margin level of the lower right first molar of all rats. Alveolar bone loss was evaluated by light microscopic analysis and analyzed using software Image J. The results were submitted to the analysis of variance (ANOVA) and Tukey’s posttest (p<0.05). The analysis revealed that there was a higher bone loss in diseased sites as compared with healthy sites. A significant reduction in the alveolar bone resorption was observed in group 2 (nimesulide) as compared with group 1 (homeopathy) 7 days after the induction of periodontitis. Our data provided evidence that homeopathy does not decrease alveolar bone loss as opposed to nimesulide in experimentally induced periodontitis.